Pharmacist Impact on Physician Practices Related to Diabetes Management - Ammar , Amina; Darghali, Lindsay M.; Tarraf, Wassim; Berlie, Helen D.; Jaber, Linda A. (Advances in Social Sciences Research Journal, 2021)
To examine the impact of a pharmacist’s physical presence on (1) the achievement of individual and combined targets for hemoglobin A1c (A1C), blood pressure (BP), and low-density lipoprotein cholesterol (LDL-C) (composite target), and (2) physician practices in relation to the American Diabetes Association (ADA) standards of medical care. Methods A retrospective, comparative study of randomly selected diabetic patients seen within an underserved primary care setting at least twice annually between June 1, 2018- December 31, 2019. Patients were allocated by whether they had received care in one of the physician-pharmacist clinics (Group A) or the physician-only clinic (Group B). Study outcomes included the proportion of patients achieving the composite and individual treatment targets for A1C, BP, and LDL-C. Results A total of 394 patients were included; Majority were underserved African Americans. The composite target was attained by 20% of participants in Group A and 13% in Group B (p=0.09). There were no statistically significant differences in achievement of individual targets between groups. A significantly higher proportion of participants in Group A achieved better control of diastolic blood pressure control (85% vs. 74%), had microalbuminuria tested (50% vs. 12%), were prescribed aspirin (43% vs. 32%), and had lower utilization of non-insulin glucose-lowering agents relative to those in Group B. Conclusion The impact of a pharmacist’s physical presence on physician practice demonstrated a general trend towards improvement in clinical outcomes related to diabetes management. Future studies are needed to further characterize the impact provided by the physician-pharmacist relationship.